2017
DOI: 10.1186/s12902-017-0203-5
|View full text |Cite
|
Sign up to set email alerts
|

Multihormonal pituitary adenoma concomitant with Pit-1 and Tpit lineage cells causing acromegaly associated with subclinical Cushing’s disease: a case report

Abstract: BackgroundA functional pituitary adenoma can produce multiple anterior-pituitary hormones, such as growth hormone (GH) -producing adenomas (GHoma) with prolactin or thyrotropin stimulating hormone production in the same lineage. However, it is very rare that acromegaly shows subclinical Cushing’s disease (SCD) beyond the lineage. Here we describe the involvement of intratumoral coexistence with 2 types of hormone-producing cells associated with different lineage in acromegaly concomitant with SCD.Case presenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…The rare entity of multiple synchronous pituitary adenomas has been defined as morphologically and immunohistologically distinct adenomas in the same patient. To date, there have been at least 18 case reports, including this one, of patients with multiple synchronous pituitary adenomas, including collision tumors in which 2 histologically distinct tumors occur at the same anatomic site (8)(9)(10)(11). With the increasing availability of higher resolution MRI that increases the sensitivity of detection for pituitary microadenomas, the detection of such multiple synchronous pituitary adenomas may increase over time (12).…”
Section: Discussionmentioning
confidence: 98%
“…The rare entity of multiple synchronous pituitary adenomas has been defined as morphologically and immunohistologically distinct adenomas in the same patient. To date, there have been at least 18 case reports, including this one, of patients with multiple synchronous pituitary adenomas, including collision tumors in which 2 histologically distinct tumors occur at the same anatomic site (8)(9)(10)(11). With the increasing availability of higher resolution MRI that increases the sensitivity of detection for pituitary microadenomas, the detection of such multiple synchronous pituitary adenomas may increase over time (12).…”
Section: Discussionmentioning
confidence: 98%
“…This unique tumor entity may be the result of PitNET clone cells undergoing various multidirectional differentiations. 28,32,33 Previously, this mixedlineage PitNET was described using various terms, such as multihormonal adenomas, 9,28,34,35 double (collision) adenomas, 11 synchronous multiple adenomas, 10 or adenomas with lineage infidelity. 36 Prior definitions primarily relied on immunohistochemical analysis of pituitary hormones or the relative positioning of tumor cell clusters observed under a microscope.…”
Section: Discussionmentioning
confidence: 99%
“…The most frequent associations are with GH and PRL or LH and FSH [11]. GH-producing adenomas with concomitant ACTH production are extremely rare, although they have been reported previously in a few cases [12][13][14][15][16][17][18][19][20]. Clinically, the majority of PHAs are silent, and diagnosis almost always relies on immunohistochemical analysis of the tumor tissue to demonstrate positivity for unrelated hormones [8,9].…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, the majority of PHAs are silent, and diagnosis almost always relies on immunohistochemical analysis of the tumor tissue to demonstrate positivity for unrelated hormones [8,9]. Roca et al [20] recently reviewed the literature on PHAs and reported 21 cases with ACTH-GH plurihormonal pituitary adenoma. Of 3 Postoperative pituitary MRI revealing residual isointense enhancement of the tumor in the sella and along the stalk measuring 9.9 × 9.9 mm in the anteroposterior (AP) and transverse dimensions and 1.3 cm in the craniocaudal (CC) dimension.…”
Section: Discussionmentioning
confidence: 99%